THE EFFECTIVENESS OF PROBIOTIC LOZENGES LACTOBACILLUS REUTERI PRODENTIS IN INCREASING SALIVARY SECRETION : Efektivitas Tablet Hisap Probiotik Lactobacillus Reuteri Prodentis Terhadap Sekresi Saliva - I Gusti Ayu Dewi Haryani; Dwis Syahriel; Zackariya Abdurrafi Ramza Patterson (Fakultas Kedokteran Gigi, Universitas Mahasaraswati Denpasar, 2022)
Introduction: Indonesian people experience dental and oral health problemsas much as 57.6%, one of the dental and oral health problems that is oftentreated is periodontal disease. Alternative prevention of periodontal disease isby consuming probiotics (Lactobacillus reuteri). Probiotic (Lactobacillusreuteri) contains L. reuteri bacteria which inhibits periodontal and cariogenicpathogenic bacteria so that it is suspected to increase salivary flow rate. Objectives: to determine the effectiveness of probiotics (Lactobacillus reuteri) to increase salivary secretion. Materials and methods: this studyused an experimental approach with a pre-test and post-test design. The research subjects were 30 students of the Faculty of Dentistry, MahasaraswatiDenpasar University who met the research criteria. The sample was dividedinto two groups, namely the group that consumed the probiotic Interlac Pro-D lozenges and the group that consumed a placebo. The data taken werethe salivary flow rate, which was measured twice, before and after administration of the probiotic Interlac Pro-D lozenges and placebo. Dataanalysis: data is processed using paired t-test and independent t-test. Resultsand Discussion: The results showed that the average salivary secretion before consuming Interlac Pro-D probiotic tablets was 0.3073 ± 0.02492 ml/minute, increasing to 0.328 ± 0.03299 ml/minute, placebo increasing to 0.276± 0.02293 ml/minute to 0.2853 ± 0.0256 ml/minute. There was a differencein the effectiveness of increasing salivary secretion between the groups consuming the probiotic Interlac Pro-D tablets and placebo (p <0.005). Conclusion: taking probiotic lozenges Interlac Pro-D (Lactobacillus reuteriprodentis) is effective in increasing salivary secretion which is beneficial forpreventive therapy of periodontal disease.